Распад метастабильной жидкости при электрическом взрыве металлических фольг; Известия вузов. Физика; Т. 60, № 8 - Орешкин В. И. Владимир Иванович; Жигалин А. С. Александр Сергеевич; Русских А. Г. Александр Геннадиевич; Чайковский С. А. Станислав Анатольевич; Бакшт Р. Б. Рина Борисовна (2017, 2017)
Заглавие с экрана